Pelaksanaan Ekstrakulikuler Pramuka di SMA Negeri 1 Muaradua – Ogan Komering Ulu Selatan - Nazarudin, Mgs; Ibrahim, Ibrahim; Apriske, Yanche (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2024)
Abstract: This article is entitled Extracurricular Implementation of Scouting at SMA Negeri 1 Muaradua, South Ogan Komering Ulu Regency-South Sumatra. This study aims to describe the implementation of extracurricular activities in the field of scouts at SMA Negeri 1 Muaradua. This study used a qualitative approach with a descriptive type, the key informants of this study were principals, scout coaches, and students. Data collection techniques used are observation, interviews, and documentation. This research will be conducted on March 9-31, 2023. The results of the research that have been obtained by researchers that there are several supporting factors and inhibiting factors, extracurricular implementation is carried out once, namely on Saturdays at 10:00-12:00, scout extracurricular implementation is followed by all classes XI-XII, Scouts have an interest and talent in participating in Pramka extracurricular activities, but there are still Scouts who lack in SIPLIN and rarely participate in Scout extracurricular activities.Keywords: Extracurricular Implementation, ScoutingAbstrak: Artikel ini berjudul Pelaksanaan Ekstrakulikuler Pramuka Di SMA Negeri 1 Muaradua Kabupaten Ogan Komering Ulu Selatan-Sumatera Selatan. Peneitian ini bertujuan untuk mendeskripsikan pelaksnaan kegiatan ekstrakulikuler di bidang pramuka Di SMA Negeri 1 Muaradua. Penelitian ini menggunakan pendekatan kualitatif dengan jenis deskriptif, kunci informan dari penelitian ini adalah kepala sekolah, pembina pramuka, dan siswa. Teknik pengumpulan data yang di gunakankan adalah observasi, wawancara, dan dokumentasi. Penelitian in di lakukan pada tanggal 9-31 Maret 2023. Hasil penelitian yang telah di peroleh oleh peneliti bahwasanya ada beberapa faktor pendukung dan faktor pengahambat, pelaksanaan ekstrakulikuler di laksanakan seinggu sekali yaitu pada hari sabtu jam 10:00-12:00, pelaksanaan ekstrakulikuler pramuka di ikuti oleh seluruh kelas XI-XII, anggota pramuka memiliki minat dan bakat dalam mengikuti pelaksanaan ekstrakulikuler pramka, akan tetapi masih adanya anggota pramuka yang kurang di siplin dan jarang mengikuti pelaksanan ekstrakuikuler pramuka.Kata kunci: Pelaksanaan Ekstrakulikuler, Pramuka